A new alternative to treat swine influenza a virus infection: Extracts from Terminalia chebula Retz - Hongbo Ma; Yunpeng Diao; Danyu Zhao; Kun Li; Tingguo Kang (African Journal of Pig Farming, 2014)
Currently, a pandemic swine influenza A virus infection causes a huge negative impact on human beings all over the world. However, the methods of treatment are not satisfactory, therefore it is urgent for us to set up new theory and practice to fight against the intractable virus. Terminalia chebula Retz, as a kind of traditional Chinese medicine, widely distributes and has multiple pharmacological effects. Evidences in laboratory and clinic practice confirm us to the potential of Terminalia chebula Retz inhibiting influenza A virus infection. We thus hypothesize that acetone extracts (tannic acids, A) of Terminalia chebula Ret may as a new alternative treat influenza A infection based on holistic concept of traditional Chinese medicine principle.